Influence of Thermal Treatment of Moroccan Red Clay on its Physicochemical and Mechanical Behavior - Harech, M. A.; Labbilta, T.; Abouliatim, Y.; Elhafiane, Y.; Benhammou, A.; Abourriche, A.; Smith, A.; Nibou, L.; Mesnaoui, M. (Clays and clay minerals, 2022)
Red clay is considered to be of significant value to the economy in Morocco, particularly in the Safi region, because of its abundance. This raw material has long been known for its quality in the manufacture of clay materials, but its use was limited to traditional ceramics. The red clay raw material was the subject of the current study with the objective of opening new industrial applications that will give added value to the Safi red clay. The physicochemical, mineralogical, and thermal properties of the Moroccan red clay were determined by X-ray fluorescence (XRF), inductively coupled plasma-atomic emission spectroscopy (ICP-AES) analysis, X-ray diffraction (XRD), oriented aggregate, and particle-size analyses, powder density by helium pycnometry, carbonate content using the Bernard method, differential thermal analysis (TG–DTA), and the BET surface area. The compacted dry powder particles were calcined at three sintering temperatures: 900, 1000, and 1100°C for 2 h. The effect of sintering temperature on ceramic properties, such as apparent porosity, water adsorption, bulk density, and mechanical strength, was examined. Dense ceramics with lower porosity and greater mechanical resistance (~300%) were produced by increasing the sintering temperature from 900 to 1100°C. The conclusion was that the evolution of physicochemical and thermal properties is related to mineralogical changes, which show that anorthite is the major phase at higher temperatures.